THE LIBERATION OF CUSTOMERS FROM MONEYLENDERS CASE STUDY OF BAITUL MAAL WA TAMWIL (BMT) ALMAUN BERKAH MADANI - Fitri Drasmawita; Sri Herianingrum (Universitas Airlangga, 2020)
This study aims to find out the role of BMT Almaun Berkah Madani in assisting the customers from the trap of moneylenders. This BMT is also expected to reduce the anxiety of some people who have financial limitations. This research approach is qualitative and using case study strategies. Data collection techniques were using direct observation in the fieldwork. Based on the results, this study found that the financing procedure at BMT Almaun Berkah Madani uses qardhul hasan financing funds. Customers get qardhul hasan funds a number of debts to money lenders. With the system, the customer places a guarantee on one of the assets owned, pays the principal installments to the BMT, and is obliged to become a member of the BMT. Thus the role of BMT with its financing products has a significant influence on improving the welfare of people who have financial limitations and helps to alleviate debts to moneylenders.Keywords: Role, BMT, Moneylenders, Qardhul Hasan Financing